Social construction of skill: an analytical approach toward the question of skill in cross-border labour mobilities - Liu-Farrer, Gracia; Yeoh, Brenda S.; Baas, Michiel (Journal of ethnic and migration studies, 2021)
Selecting labour migrants based on skill has become a widely practised migration policy in many countries around the world. Since the late twentieth century, research on 'skilled' and 'highly skilled' migration has raised important questions about the value and ethics of skill-based labour mobility. More recent research has begun to question the concept of skill and skill categorisation in both government policy and academic research. Taking the view that migrants' skill is socially constructed, we centre our discussion on three questions: Who are the arbitrators of skill? What constitutes skill? And how is skill constructed in the migration process and in turn, how does skill affect the mobility? We show that diverse actors are involved in the process of identifying, evaluating and shaping migrant skill. The interpretation of migrants' skill is frequently distorted by their ascriptive characteristics such as race, ethnicity, gender and nationality, reflecting the influence of colonial legacy, global inequality as well as social stratification. Finally, this special issue emphasises the complex, and frequently reciprocal, relationship between skill and mobility.